If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 1)(4x + -3) = 0 Reorder the terms: (1 + 4x)(4x + -3) = 0 Reorder the terms: (1 + 4x)(-3 + 4x) = 0 Multiply (1 + 4x) * (-3 + 4x) (1(-3 + 4x) + 4x * (-3 + 4x)) = 0 ((-3 * 1 + 4x * 1) + 4x * (-3 + 4x)) = 0 ((-3 + 4x) + 4x * (-3 + 4x)) = 0 (-3 + 4x + (-3 * 4x + 4x * 4x)) = 0 (-3 + 4x + (-12x + 16x2)) = 0 Combine like terms: 4x + -12x = -8x (-3 + -8x + 16x2) = 0 Solving -3 + -8x + 16x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -4x)(3 + -4x) = 0Subproblem 1
Set the factor '(-1 + -4x)' equal to zero and attempt to solve: Simplifying -1 + -4x = 0 Solving -1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 0 + 1 -4x = 0 + 1 Combine like terms: 0 + 1 = 1 -4x = 1 Divide each side by '-4'. x = -0.25 Simplifying x = -0.25Subproblem 2
Set the factor '(3 + -4x)' equal to zero and attempt to solve: Simplifying 3 + -4x = 0 Solving 3 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4x = 0 + -3 -4x = 0 + -3 Combine like terms: 0 + -3 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75Solution
x = {-0.25, 0.75}
| 170=2x+10x | | 3x-4+x+3= | | 24v^6w^3-375=0 | | (6r-48)(48r-6)=0 | | 2x^3+5x^2+7x=0 | | 6y-3(y-1)+5= | | -4log(2x)+9=3.6 | | -4+x^2= | | 3s(5s-3)(3s-1)=0 | | 2x+1/2x=66 | | x+2(x-3)=-(x-2) | | (4x+20)=(2x+50) | | 2-4-11+12-7-6+3= | | 4x=-8x | | (3m+5n)(3m+5n)-(2n)(2n)=0 | | (v)+2=7 | | 2=10+3z | | 250+1/6=693 | | (192-3x)+13/4=128+3*(6-14x)/4 | | z^2+22z+40= | | 250+1/6 | | 15x^2-124x+160=0 | | (2x+50)+(4x+20)=180 | | v=brt | | 5a-3=7a+7+3 | | 7=5y | | 489.8=3.33*3.14*36h | | 5x-9=45x+15 | | x+(v*v)=(w*w) | | (2x-3y)(2x-3y)+12xy=0 | | 8y-7-6y+4=0 | | 7+5x=-x+1 |